Nutritional status of adult hemodialysis patients in Al-Najaf Al-Ashraf Governorate - Kadhum, Ibrahem; Mohammed, Widad (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To assess the nutritional status of hemodialysis patients. Methodology: A descriptive quantitative cross sectional study was effectuated in hemodialysis centers from February 2011 to September 2011. A purposive "non-probability" sample of (70) male and female hemodialysis patients in al-Najaf al-Ashraf Governorate from those who have spent more than six months on maintenance hemodialysis schedule. Data collected through using of a well-designed questionnaire consist of five parts, part one consists of sociodemographic contain (9) items, and part two consists of medical data contain (8) items, and part three consists of health and nutrition behavior contain (12) items plus (8) items of anthropometric measurements, and part four consists of food frequency contain (5) major items, and part consist of laboratory investigation contain (9) items. In addition to food diary (24 hour dietary recall) used for validating the food frequency part. Data collected by direct interview method with ESRD on maintenance hemodialysis patients’ also by anthropometric measurement method and blood sample for laboratory investigation. Reliability of the questionnaire was determined through pilot study and validity determined through a panel of experts consists of (18) experts. Data was analyzed by using of descriptive data analysis (frequencies, percentages, mean, standard deviation and relative sufficiency) and by using of inferential analysis (correlation coefficient, t- test and χ²). Results: The study results indicates that the majority of study sample suffer from moderate malnutrition according to several indicators including anthropometric measurements, laboratory investigations and (type and quality) of food. Most of study sample was illiterate, and the sample divided between male and female with invisible variance between percentages, the majority of study sample was nutritionally instructed but they don’t reflect the desired compliance. Recommendations: The study recommends with the necessity of establish a nutritional health style for hemodialysis patients including several dialogist like calibrating of dietary intake, increase physical exercise as tolerated, control body weight and enrich the list of laboratory investigations. Workout anew studies about the studied phenomenon, activate the role of dietician (doctor and nurse) in hemodialysis centers, hemodialysis malnutrition alert day and initiate a proper financial support through establish a hemodialysis malnutrition foundation work for improvement of socioeconomic status and nutritional status through study subjects